Tingkat Kecemasan Pasien Kanker yang Menjalani Kemoterapi di Masa Pandemi Covid-19: Literature Review - Liska Lihawa; Ricky Zainuddin (Universitas Baiturrahim, 2022)
The high morbidity and mortality of Covid-19 causes fear and anxiety about the risk of exposure to this disease in everyone, including cancer patients. Objective: To identify the anxiety level of cancer patients undergoing chemotherapy during the Covid-19 pandemic. Methods: Article searches through Pubmed, ProQuest, ScienceDirect, Wiley, and Google Scholar identified 20,489 articles, then restricted based on inclusion criteria: a study with samples of cancer patients undergoing chemotherapy during the Covid-19 pandemic; a study that assessed the anxiety level of cancer patients undergoing chemotherapy during the Covid-19 pandemic; published in the last three years; have full text in English and Indonesian, so that 6 articles are obtained. Results: Of the six articles reviewed, one study reported that during Covid-19 all cancer patients undergoing chemotherapy experienced increased anxiety (57%); two studies reported severe anxiety (36.7%; p=0.000 and 33%); two studies reported moderate anxiety with respective scores (22.3; p=0.000; and 18.5; p=0.037); and one study of mild anxiety (25.8% women and 16.8% men; p=0.159). Anxiety experienced by patients is caused by a number of factors, including fear of being infected with Covid-19, type of cancer, age and gender, delays or changes in treatment and treatment plans, excessive exposure to information, uncertainty over the end of Covid-19, lack of understanding and information related to Covid -19, hospital restrictions, and feelings of loneliness. Conclusion: Based on the results of a review of six articles, it was concluded that cancer patients undergoing chemotherapy during the Covid-19 pandemic experienced anxiety that varied from mild to severe anxiety depending on the influencing factors